Delivery room resuscitation and short-term outcomes of extremely preterm and extremely low birth weight infants: a multicenter survey in North China. Issue 13 (5th July 2021) - Li, Shuai-Jun; Feng, Qi; Tian, Xiu-Ying; Zhou, Ying; Ji, Yong; Li, Yue-Mei; Zhai, Shu-Fen; Guo, Wei; Zhang, Fang; Zheng, Rong-Xiu; He, Hai-Ying; Liu, Xia; et al.
Abstract: Background: Delivery room resuscitation assists preterm infants, especially extremely preterm infants (EPI) and extremely low birth weight infants (ELBWI), in breathing support, while it potentially exerts a negative impact on the lungs and outcomes of preterm infants. This study aimed to assess delivery room resuscitation and discharge outcomes of EPI and ELBWI in China. Methods: The clinical data of EPI (gestational age [GA] <28 weeks) and ELBWI (birth weight [BW] <1000 g), admitted within 72 h of birth in 33 neonatal intensive care units from five provinces and cities in North China between 2017 and 2018, were analyzed. The primary outcomes were delivery room resuscitation and risk factors for delivery room intubation (DRI). The secondary outcomes were survival rates, incidence of bronchopulmonary dysplasia (BPD), and risk factors for BPD. Results: A cohort of 952 preterm infants were enrolled. The incidence of DRI, chest compressions, and administration of epinephrine was 55.9% (532/952), 12.5% (119/952), and 7.0% (67/952), respectively. Multivariate analysis revealed that the risk factors for DRI were GA <28 weeks (odds ratio [OR], 3.147; 95% confidence interval [CI], 2.082–4.755), BW <1000 g (OR, 2.240; 95% CI, 1.606–3.125), and antepartum infection (OR, 1.429; 95% CI, 1.044–1.956). The survival rate was 65.9% (627/952) and was dependent on GA. The rate of BPD was 29.3% (181/627). Multivariate analysis showed that the risk factors for BPD were male (OR, 1.603; 95% CI, 1.061–2.424), DRI (OR, 2.094; 95% CI, 1.328–3.303), respiratory distress syndrome exposed to ≥2 doses of pulmonary surfactants (PS; OR, 2.700; 95% CI, 1.679–4.343), and mechanical ventilation ≥7 days (OR, 4.358; 95% CI, 2.777–6.837). However, a larger BW (OR, 0.998; 95% CI, 0.996–0.999), antenatal steroid (OR, 0.577; 95% CI, 0.379–0.880), and PS use in the delivery room (OR, 0.273; 95% CI, 0.160–0.467) were preventive factors for BPD (all P  < 0.05). Conclusion: Improving delivery room resuscitation and management of respiratory complications are imperative during early management of the health of EPI and ELBWI.